HERO CONSTRUCTION NARRATIVE IN A BUG'S LIFE, THE FILM - Pradhana, Dhea Restu (2013)
The present study entitled Hero Construction Narrative in A Bug's Life, The Film aims to investigate the film narrative of hero construction. The study employs a descriptive qualitative study with textual analysis. The present study adopted Hourihan's (1997) theory as its major theoretical framework and the language of film theory (Heintz and Stracey, 2006). The study found that the hero construction in the film is presented through three phases there are the initiation phase, the conflict phase and the resolution phase. These phases are also analyzed through the language of the film. These phases are crafted through the pattern of cause and effect where film characters become the agent of causality. These characters are put in binary opposition to construct the hero in the narrative which is mediated through the language of film, such as camera shots, camera movement and mise en scène. The uses of binary opposition support the delivery of the didactic message in the film, since animation films are often directed to children. Keywords: film, animation film, narrative cinema, hero construction, children's literature Studi ini berjudul Narasi Pembentukan Pahlawan pada Film A Bug's Life bertujuan untuk menginvestigasi pembentukan pahlawan dalam film. Studi ini menggunakan studi deskriptif kualitatif dengan analisis teks. Studi ini mengadopsi teori yang dikemukakan oleh Hourihan (1997) sebagai landasan utama dan teori bahasa film yang dikemukakan oleh Heintz dan Stracey (2006). Studi ini menemukan bahwa pembentukan pahlawan dalam film ditampilkan melalui tiga fase yakni fase inisiasi, fase konflik dan fase resolusi. Ketiga fase ini juga dianalisis melalui bahasa film. Ketiga fase ini dibentuk melalui pola sebab akibat dimana karakter dalam film berperan sebagai agen kausalitas. Karakter-karakter tersebut di posisikan dalam oposisi biner untuk membentuk sang pahlawan dalam narasi yang ditampilkan melalui bahasa film yakni camera shots, camera movement dan mise en scène. Penggunaan oposisi biner mendukung dan memudahkan penyampaian pesan didaktis film, karena film animasi biasanya ditujukan untuk anak-anak. Kata Kunci: film, film animasi, naratif sinema, pembentukan pahlawan, sastra anak